Hybrid localization techniques for GSM-WCDMA cellular radio system: article / Ukasyah Mahamod - Mahamod, Ukasyah (2013)
Location Based Services (LBS) is an important features in the cellular radio network such as Global System for Mobile Communications (GSM), Wideband Code Division Multiple Access (WCDMA) and Long Term Evolution (LTE). The accuracy of positioning or localization in such single layer network network depend on the Location Determination Technique or Technology (LDT) implemented; the Enhanced Observed Time Difference (E-OTD) in GSM and Observed Time Difference Of Arrival (OTDOA) for WCDMA but subjected to signal hearability from at least three Base Station (BSs) or NodeBs. This paper present hybrid localization techniques for a multilayer or heterogeneous GSM-WCDMA network when a single layer network experience low signal hearability. This can be resolve by gathering at least three signal hearability from multilayer network infrastructure or using previous location information to reduce LDT error. The proposed method has been implemented and evaluated using simulation under various mobility models. Simulation shown that the LDT error for hybrid technique can been improved as compared to E-OTD and OTDOA and met E911 requirement.